Grounded Capacitor Oscillators Using A Single Operational Transconductance Amplifier - Muhammad Taher Abuelma'atti; Muhammad Haroon Khan (Active and Passive Electronic Components)
New oscillator circuits using operational transconductance amplifiers (OTAs) are presented. Each circuit uses a single OTA and grounded capacitors. The feasibility of obtaining oscillators with independent control of frequency and oscillation is considered. Also, the feasibility of exploiting, to advantage, the frequency dependence of the OTA-transconductance is considered. This may result in OTA-based RC oscillators using only one externally-connected capacitor.